The Influence of Moldova’s Economic Performance on EU Integration: Array - Pirju, Ionel Sergiu (Acta Universitatis Danubius. Relationes Internationales, 2020)
The Republic of Moldova, a state located in the eastern proximity of the European Union, divides its political options between the mirage of the West and the traditional influence of the Russian Federation. The former Soviet republic with a majority of Romanian-speaking population is one of the countries that has been progressed the least since the fall of communism. Excessive bureaucracy, widespread political corruption in all political parties, both pro-European and pro- Russian, border insecurity has seriously damaged long-term performance of this small country. The economy based mainly on agricultural production does not give to the Republic of Moldova enough independence to get out of the sphere of influence demanded by the main international decisionmakers. The intention of this study is to analyze if the economic performance of this country is the main impediment for acceptance in the structures of the European Union.